2018
DOI: 10.1016/s2468-2667(18)30141-5
|View full text |Cite
|
Sign up to set email alerts
|

Social connectedness and engagement in preventive health services: an analysis of data from a prospective cohort study

Abstract: SummaryBackgroundEvidence of the possible health benefits of social connectedness is increasing. We aimed to examine poor social connectedness as a possible barrier to participation in preventive health services among older people (aged 53–69 years).MethodsWe analysed data from a prospective cohort study of 5362 socially stratified births from the Medical Research Council National Survey of Health and Development enrolled in England, Scotland, and Wales in March 1946. At ages 68–69 years, participants reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 31 publications
(51 reference statements)
3
45
0
Order By: Relevance
“…This variable ranged from 0 (where study members attended no health checks) to 1 (where study members attended 6 out of 6 checks). A summary measure of all health checks was used to capture engagement with preventive health care rather than to explore the predictors of individual health checks (which were not expected to vary [41]).…”
Section: Methodsmentioning
confidence: 99%
“…This variable ranged from 0 (where study members attended no health checks) to 1 (where study members attended 6 out of 6 checks). A summary measure of all health checks was used to capture engagement with preventive health care rather than to explore the predictors of individual health checks (which were not expected to vary [41]).…”
Section: Methodsmentioning
confidence: 99%
“…14 Social factors such as relationship status and social contact networks are also related to BMI and other aspects of health. 57 Higher BMI is associated with stigma, discrimination, lower self-esteem, and physical and mental ill-health 815 , all of which could potentially affect social, educational, and employment outcomes, meaning that the relationships between SEP, social factors and BMI could be bidirectional. A study conducted by Flint et al 16 demonstrated considerable weight bias in the recruitment process; employers across various sectors rated the same curriculum vitae as less suitable for a job when it was accompanied by a photograph of a person with obesity, particularly a woman with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that social connectedness can be a powerful phenomenon to tap into when planning for public health interventions. Improved mental health, reduced depression, enhanced sense of belonging, improved health-seeking behaviour, reduced stress, enhanced self-esteem, and improved cognition are all notable bene ts of social connectedness (3,(8)(9)(10)(11)(12). Evidence has shown that people with decreased social connectedness have poor mental and physical health and higher morbidity and mortality compared to those with strong social connectedness (8)(9)(10)(11)13).…”
Section: Introductionmentioning
confidence: 99%